Tingkat Infestasi Aphelenchoides besseyi pada Benih Padi di Bogor - Fitrianingrum Kurniawati; Supramana Supramana (Jurnal Fitopatologi Indonesia, 2016)
The white tip disease on rice plants have been discovered in the district of Bogor, i.e. in  Sukamakmur, Petir, and Muara Experimental Station areas. The infected plant exhibited symptoms, involving whiten leaf tip 3–5 cm that later  turn to necrosis, twisted and crinkled. The disease is supposed caused by a parasitic nematode, namely Aphelenchoides besseyi, which is known seed borne. Extraction of nematodes based on  ISTA protocols on rice was conducted.  Seeds from eight varieties, SL8SHS, Hybrid Rice (HIPA14), IPB 3S, IR-64, Pertiwi (Pak Tiwi), Inpari 31, Pandan Wangi Bogor (Sintanur) and Ciherang, was obtained from seed vendors in Bogor and Muara Experimental Station. The majority of nematodes recovered were females and only few males with morphological characteristics matching with A. besseyi.  All seed rice varieties tested contained A. besseyi with the average of 3–341 nematodes per 5 g seed.